2022
DOI: 10.7554/elife.82437
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial T6SS effectors with a VRR-Nuc domain are structure-specific nucleases

Abstract: The type VI secretion system (T6SS) secretes antibacterial effectors into target competitors. Salmonella spp. encode five phylogenetically distinct T6SSs. Here we characterize the function of the SPI-22 T6SS of Salmonella bongori showing that it has antibacterial activity and identify a group of antibacterial T6SS effectors (TseV1-4) containing an N-terminal PAAR-like domain and a C-terminal VRR-Nuc domain encoded next to cognate immunity proteins with a DUF3396 domain (TsiV1-4). TseV2 and TseV3 are toxic when… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…parahaemolyticus ( Jana et al ., 2019 ), IdrD from Proteus mirabilis ( Sirias et al ., 2020 ), RhsB from Acidovorax citrulli ( Pei et al ., 2022 ), and TseV from P . aeruginosa and Salmonella bongori ( Wang et al ., 2021 ; Hespanhol et al ., 2022 ). In addition, SitA3 involved in interbacterial antagonism via outer membrane exchange contains the conserved αβββαβ fold ( Vassallo et al ., 2017 ).…”
Section: Pd-(d/e)xk Superfamilymentioning
confidence: 99%
See 3 more Smart Citations
“…parahaemolyticus ( Jana et al ., 2019 ), IdrD from Proteus mirabilis ( Sirias et al ., 2020 ), RhsB from Acidovorax citrulli ( Pei et al ., 2022 ), and TseV from P . aeruginosa and Salmonella bongori ( Wang et al ., 2021 ; Hespanhol et al ., 2022 ). In addition, SitA3 involved in interbacterial antagonism via outer membrane exchange contains the conserved αβββαβ fold ( Vassallo et al ., 2017 ).…”
Section: Pd-(d/e)xk Superfamilymentioning
confidence: 99%
“…The VRR-Nuc (virus-type replication repair nuclease) domain is found in enzymes involved in interstrand DNA crosslink repair ( Kratz et al ., 2010 ; Liu et al ., 2010 ; MacKay et al ., 2010 ; Smogorzewska et al ., 2010 ; Gwon et al ., 2014 ; Wang et al ., 2014 ; Zhao et al ., 2014 ), but recent studies identified effectors containing this domain - named TseVs (type VI effector VRR-Nuc) ( Wang et al ., 2021 ; Hespanhol et al ., 2022 ). TseV2 and TseV3 from S .…”
Section: Pd-(d/e)xk Superfamilymentioning
confidence: 99%
See 2 more Smart Citations
“…Next, were two oral presentations from submitted abstracts. Julia Takuno Hespanhol, a Master's student from Ethel Bayer‐Santos laboratory (ICB/USP) presented their recent work describing antibacterial toxins secreted by a T6SS from Salmonella bongori that function as endonucleases, generating double‐strand breaks in the DNA of target cells (Hespanhol et al, 2022). Letícia Franco, a post‐doc from Mario Henrique Barros group (ICB/USP) discussed work performed with Alexander Tzagoloff (Columbia University, USA) describing the mechanisms of assembly of cytochrome oxidase and ATP synthase in Saccharomyces cerevisiae .…”
mentioning
confidence: 99%